Graphene near infrared-I/II probe in two-photon excitation-wavelength-independent photoluminescence and photoinactivation. (30th June 2022) - Kuo, Wen-Shuo; Wu, Ping-Ching; Chang, Chia-Yuan; Wang, Jiu-Yao; Chen, Pei-Chi; Hsieh, Miao-Hsi; Lin, Sheng-Han; Cheng, Jen-Suo; Chou, Yu-Tsung
Abstract: Nitrogen doping and amino-group functionalization through chemical modification can engender enhance electron donation. Using a homemade femtosecond titanium:sapphire laser optical system operated at a low energy and short photoexcitation time [power: 200.0 nJ pixel −1 ; scanning frequency: 150 scans (∼0.80–1.33 s); excitation wavelength: 870, 910, or 970 nm], this study conducted these processes on the large π-conjugated system of graphene quantum dot (GQD)-based materials functioning as electron donors; this improved the efficiency of charge transfer to the prepared amino-N-GQDs, resulting in enhanced two-photon absorption, excitation-wavelength-independent photoluminescence (EWI-PL), radiative efficiency, excitation absolute cross section, and excitation from the near-infrared (NIR)-I to the NIR-II region. The lifetime decreased and quantum yield (QY) increased. The sorted amino-N-GQDs exhibited two-photon EWI-PL emissions between the ultraviolet and NIR-I regions, leading to the generation of reactive oxygen species (ROS), which functioned as two-photon photosensitizers for photodynamic therapy (PDT). Increasing the mean lateral size of the particles increased the N-functionality-dependent photochemical and electrochemical activities, which improved the PL QY and thus enhanced the efficiency of two-photon PDT. Additionally, a polystyrene sulfonate (PSS) coating was applied (forming sorted amino-N-GQD-PSS); the sulfur atoms introduced by the PSS induced the radiative recombination of localized electron–hole pairs and then improved the sorted amino-N-GQD surfaces by strengthening the quantum confinement of their emissive energy. Thus, compared with the sorted amino-N-GQDs that were not coated, the PSS-coated materials had superior two-photon properties. No ROS were detected. Accordingly, these materials are suitable for use as two-photon contrast probes for analyte tracking and localization. Graphical abstract: Image 1